2020
DOI: 10.1177/0034355220902242
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Employment Outcomes for Older Adults With Disabilities in Korea

Abstract: Although older adults with disabilities have a need and desire to be productive, for many this takes the form of work, they often face barriers in finding and maintaining employment. To improve understanding of employment characteristics and needs for older adults with disabilities in Korea, this study examined their employment rates (ER) from a life-span perspective. A dataset on individuals from age 41 to 75 ( N = 4,211) from the Panel Survey of Employment for the Disabled (PSED), collected by the Korea Empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Individuals in the oldest age group were most unlikely to say that they like their current activities and that they did not think they would enjoy work. Previous research found that working individuals past retirement age believed their work to be important, did not want to retire, had a need for productivity, and benefitted from on‐the‐job social interactions (David et al, 2015; Halvorsen & Yulikova, 2020; Lee et al, 2020). However, they also reported experiences of ageism, which could explain our finding that older individuals were most likely to report that they did not want to work due to a belief that they would not join the experience.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals in the oldest age group were most unlikely to say that they like their current activities and that they did not think they would enjoy work. Previous research found that working individuals past retirement age believed their work to be important, did not want to retire, had a need for productivity, and benefitted from on‐the‐job social interactions (David et al, 2015; Halvorsen & Yulikova, 2020; Lee et al, 2020). However, they also reported experiences of ageism, which could explain our finding that older individuals were most likely to report that they did not want to work due to a belief that they would not join the experience.…”
Section: Discussionmentioning
confidence: 99%